Perceived pros and cons of smoking and quitting in hard-core smokers: a focus group study - Bommelé, Jeroen (BioMed Central, 2014)
BACKGROUND: In the last decade, so-called hard-core smokers have received increasing interest in research literature. For smokers in general, the study of perceived costs and benefits (or ‘pros and cons’) of smoking and quitting is of particular importance in predicting motivation to quit and actual quitting attempts. Therefore, this study aims to gain insight into the perceived pros and cons of smoking and quitting in hard-core smokers. METHODS: We conducted 11 focus group interviews among current hard-core smokers (n = 32) and former hard-core smokers (n = 31) in the Netherlands. Subsequently, each participant listed his or her main pros and cons in a questionnaire. We used a structural procedure to analyse the data obtained from the group interviews and from the questionnaires. RESULTS: Using the qualitative data of both the questionnaires and the transcripts, the perceived pros and cons of smoking and smoking cessation were grouped into 6 main categories: Finance, Health, Intrapersonal Processes, Social Environment, Physical Environment and Food and Weight. CONCLUSIONS: Although the perceived pros and cons of smoking in hard-core smokers largely mirror the perceived pros and cons of quitting, there are some major differences with respect to weight, social integration, health of children and stress reduction, that should be taken into account in clinical settings and when developing interventions. Based on these findings we propose the ‘Distorted Mirror Hypothesis’.